A framework to support personalising prescribed school curricula. (8th October 2018) - Prain, Vaughan; Blake, Damian; Deed, Craig; Edwards, Marie; Emery, Sherridan; Farrelly, Cathleen; Fingland, Doug; Henriksen, Joanne; Lovejoy, Valerie; Meyers, Noel; Mooney, Amanda; Muir, Tracey; et al.
Abstract : There is a recent advocacy for students to experience their learning as personalised, but this expectation poses challenges for teachers tasked with addressing prescribed curricula. In this article, we draw on relevant literature and our analyses of three case studies to propose a framework within which teachers can achieve both goals. We first clarify what we mean by personalising learning, noting problems in how it is currently conceptualised and enacted. We suggest that any attempt to support students to personalise their learning needs to be contextualised within broader curricular goals, and that its developmental nature entails progressions in specific learner capabilities, and therefore the need for students to be supported in this process. In proposing a framework for this support, we focus on general principles around the what and how of this process rather than on particular discipline areas.